2014
DOI: 10.4314/njbas.v21i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Growth Responses of Two Cultivated Okra Species (<i>Abelmoschus caillei</i> (A. Chev) Stevels and <i>Abelmoschus esculentus</i> (Linn.) Moench) in Crude Oil Contaminated Soil

Abstract: The morphological distinctiveness of two cultivated Okra species-Abelmoschus caillei and Abelmoschus esculentus was investigated using six accessions; three for each species in crude oil contaminated soil. The seeds were collected from home gardens in Benin City and NIHORT. Morpho-agronomic characters such as numbers of days from sowing to germination, plant height, stem base diameter, stem color and pubescence, leaf shape and color, number of leaves produced, growth habit, branching, fruit and fruiting charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 6 publications
(11 reference statements)
1
4
1
Order By: Relevance
“…Edebiri and Nwanokwale [10] reported that metals present in spent oil are not necessarily the same as those present in the unused lubricants; Whisman et al (1974) observed that most heavy metals like V, Pb, Al, Ni, and Fe that are below detection in unused lubricants oil gave high concentration values in used oil. This is similar to the findings of Osawaru et al [26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Edebiri and Nwanokwale [10] reported that metals present in spent oil are not necessarily the same as those present in the unused lubricants; Whisman et al (1974) observed that most heavy metals like V, Pb, Al, Ni, and Fe that are below detection in unused lubricants oil gave high concentration values in used oil. This is similar to the findings of Osawaru et al [26].…”
Section: Discussionsupporting
confidence: 93%
“…The reliance on fossil fuel to meet our energy need continue to exacerbate among other issues oil pollution due to spillage, threat to environmental integrity, and biodiversity loss [18,20,21,25,26]. Oil spills at auto mechanic workshops, electric power-generating plants, and small-and large-scale industries continued to receive insufficient research attention despite the potential for accumulation and negative effects on sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…The studies showed extreme levels of these parameters are evidence of their effect on plant growth [60]. Ogboghodo et al [62]; Osawaru et al [63,64] reported that crude oil affects the chemical characteristics of the soil leading to an increase in organic matter, and a decrease in available P. The authors further reported that the high levels of pollution caused by crude oil impeded the growth of maize. Table 1.…”
Section: Implications Of Artisanal Crude Oil Refining On Sustainable ...mentioning
confidence: 99%
“…Okra is a vegetable originally thought to have its origin from South East Asia, however, it is now widely cultivated in tropical and subtropical regions [10]. In West Africa, the wide varieties of okra cultivars are of two morphologically distinct species, the common okra, (Abelmoschus esculentus) and West African okra (Abelmoschus caillei) [11]. Okra is known as 'ilasa' in south-west Nigeria, In Igbo-Ora, Oyo state, south-west Nigeria, the speci c variety of okra it is called "ilasa kekere" and has been identi ed as A. esculentus [12].…”
Section: Introductionmentioning
confidence: 99%